Komparasi Minat Berwirausaha Bagi Penganggur Berpengalaman Kerja Sebagai TKI Dan Non TKI - Sapto Setyodhono; Zellius Ragiliawan (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2018)
Employment problems in Indonesia such as a relatively high number of unemployed and limited job opportunities. Creation and expansion of jobs opportunities are continuously pursued, both domestically and through placement of workers abroad. One of the priorities of job creation for the unemployed is to develop entrepreneurship. By processing and analyzing descriptively quantitative data of Sakernas August 2017, it is indicated that the Labor Force Participation Rate into Indonesian Migrant Workers (TKI) is higher, but the unemployment rate is also the highest compared to that experienced by non migrant workers and unemployed workers. The proportion of workers who have work experience as the most migrant workers interested in entrepreneurship, the second most are those who have non-migrant work experience, while the unemployed who have no least work experience who are interested to become entrepreneurs. Entrepreneurs to be developed by ex-migrant workers are relatively small. This is indicated by the effort that has been or is being done by the ex- migrant worker for entrepreneurship only collecting capital and looking for business location, and no one to take care of business license. Similarly, unemployed ex-migrant workers who have received job training and certified are also the fewest. Therefore, efforts to develop the potential of unemployed ex-TKI to become successful entrepreneurs need special attention.